Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1111/j.1442-200x.1979.tb00244.x
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy Indicating Nephrotic Pattern in Childhood

Abstract: During the last 4 years, we had the opportunity to examine 11 patients of IgA nephropathy in childhood, in whom stainning of IgA and Cs in mesangium area was a common finding by immunofluorescent study. Urinary analysis indicated persistent microscopic hematuria and proteinuria in all cases. 8 cases among them showed macroscopic hematuria attack during the observation period. The levels of proteinuria were usually above 1 g/day. 4 cases had massive proteinuria, hypoalubminemia and hyperlipidemia, indicating ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…8, 14], the most common clinical picture is asymptomatic hematuria (with or without proteinuria) in both of these age groups. Other relatively rare clinical manifestations reported include acute renal failure [15], acute glomerulonephritic syndrome [8], and nephrotic syndrome [7,8,16]. In the present study, nephrotic syn drome was recognized in 4 cases at admission and in 1 case in the follow-up studies.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…8, 14], the most common clinical picture is asymptomatic hematuria (with or without proteinuria) in both of these age groups. Other relatively rare clinical manifestations reported include acute renal failure [15], acute glomerulonephritic syndrome [8], and nephrotic syndrome [7,8,16]. In the present study, nephrotic syn drome was recognized in 4 cases at admission and in 1 case in the follow-up studies.…”
Section: Discussionmentioning
confidence: 48%
“…When first described by Berger [1], the amount of urine protein was observed to be less than 1.0 g/day in patients with the disease, and this finding was generally accepted by many authors [2][3][4][5][6], However, there have been several reports describing clinical features of nephrotic syndrome with massive urine protein in IgA nephropathy (7,8], At present, little information is available regarding the underlying renal histological changes and degree of proteinuria in these patients. In order to clarify the correlation between the renal lesions and the clinical feature, the final outcome of 22 patients with different degree of proteinuria of IgA nephropathy was studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the Southwest Pediatric Nephrology Study Group popula tion, it was found in 4 out of the first 83 patients with IgA nephropathy [ 19], Our review of the literature reveals a total of at least 46 patients with the combination of MCNS/IgA. These reports emanate from over 12 different countries includ ing patients from China [1,3], Japan [5] [3], and Hong Kong [3, 12, 13. 14].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have sug gested that the nephrotic syndrome bodes a poor renal prognosis in IgA nephropathy, with many nephrotic IgA patients having severe focal proliferative glomerulone phritis [7,8,12,21] or focal sclerosis [7,8,[21][22][23][24], However, recently there have been a large number of reports of IgA nephropathy patients with minimal or minor glomerular changes who had, or later developed, the nephrotic syndrome (MCNS/IgA). Several of these patients had initial renal biopsies in which immunofluo rescence studies of IgA were negative; subsequent biop sies indicated by the appearance of hematuria, hyperten sion, transient elevation of serum creatinine, frequent relapse of the nephrotic syndrome or steroid depen dence, showed mesangial deposition of IgA [1,4,5,15,18,19]. Other patients with repeat biopsies showing IgA were clinically more typical of pure MCNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation